1983
DOI: 10.1037/h0080714
|View full text |Cite
|
Sign up to set email alerts
|

The improvement of university teaching.

Abstract: Three distinct and different types of teaching improvement are identified and described. Type R (Remedial) consists of the detection and elimination of errors in teaching, such as in preparation or evaluation. Type F (Facilitative) emphasizes the use of appropriate general principles: use of objectives, frequent testing, knowledge of results, etc., to facilitate student learning. Type O (Optimizing) requires the use of a research orientation in order to determine the procedures and techniques which do, in fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…McLean suggested that poorer teachers tended to be unaware of their own classroom behaviors and thus were more in need of specific behaviorial feedback than their higher-rated colleagues. This interpretation is consistent with Sullivan's (1983) view that progressing from poor to adequate teaching requires the elimination of specific behavioral weaknesses or errors, a process that Sullivan has called remedial teaching improvement. Statistical regression was not seen as a viable interpretation of the improved performance of low-rated teachers because performance gains were restricted to time periods following the introduction of feedback and were not apparent in repeated pre-feedback measures.…”
Section: Modification Of Classroom Teaching Behaviorssupporting
confidence: 82%
“…McLean suggested that poorer teachers tended to be unaware of their own classroom behaviors and thus were more in need of specific behaviorial feedback than their higher-rated colleagues. This interpretation is consistent with Sullivan's (1983) view that progressing from poor to adequate teaching requires the elimination of specific behavioral weaknesses or errors, a process that Sullivan has called remedial teaching improvement. Statistical regression was not seen as a viable interpretation of the improved performance of low-rated teachers because performance gains were restricted to time periods following the introduction of feedback and were not apparent in repeated pre-feedback measures.…”
Section: Modification Of Classroom Teaching Behaviorssupporting
confidence: 82%
“…In so doing, the focus in instructional development practices shifts from the remediation of teaching behaviours to full partnerships with scholar-teachers characterized by their research orientation. Sullivan (1983) considered this progression from "remedial" to "optimizing" levels of instructional development as one which would most benefit student learning.…”
Section: A Scholarship Perspective In Instructional Developmentmentioning
confidence: 99%
“…For these reasons, the "basic instructional skills" approach to instructional development lacks credibility among many professors. Despite a shift away from this approach by instructional developers (Donald, 1986;Sullivan, 1983), faculty perceptions of the basic skills approach (and their reasons for not participating) persist.…”
mentioning
confidence: 99%
“…Progressing from poor to adequate lecturing requires eliminating specific behavioural weaknesses. Therefore, feedback for poorer lecturers can lead to significant improvement in perceived lecturing effectiveness (Sullivan, 1983). For instance, a group of instructors trained on a limited set of behaviours known to contribute substantially to overall lecturing effectiveness (e.g., vocal variation, facial expression, movement and gesture, use of pauses for emphasis) demonstrated significant gains in student ratings from pre-to post-test, indicating that behavioural training produced significant improvement in classroom instruction effectiveness (Murray & Lawrence.…”
Section: Implications For Higher Educationmentioning
confidence: 99%